Transformasi petani madu menjadi agripreneur di kabupaten Sumbawa - Sude Aletheia Sitorus; I Nyoman Gede Ustriyana; Gede Mekse Korri Arisena (Fakultas Pertanian Universitas Yudharta Pasuruan, 2021)
This study aims to analyze the characteristics of honey farmers who have become agripreneurs and analyze the influence of attitudes, subjective norms, behavioral control, and entrepreneurship education on the transformation of honey farmers into agripreneurs in Sumbawa Regency. The number of samples of respondents was 34 respondents who were obtained based on the saturated sample method. The model was designed based on the approach Structural Equation Modeling (SEM) based on Smart PLS version 3.0 which was analyzed through a computer program. The results showed that behavioral control and entrepreneurship education had a significant effect on the transformation of honey farmers into agripreneurs in Sumbawa Regency. Therefore, behavioral control which contains encouragement from family, relatives, motivators, and themselves to build a business needs to be improved, and also increasing entrepreneurial education activities containing seminars and entrepreneurship training is also very much needed by honey farmers to be able to transform into agripreneurs.